KEGANASAN RUMAHTANGGA DI MALAYSIA: SATU ANALISIS LITERATUR: Domestic Violence in Malaysia: Analysis of Literature Review - Mohamed Daud, Nadiah; Mat Hussin, Mohd Norhusairi; Jamaludin, Mohd Hafiz (Journal of Shariah Law Research, 2021)
The whole world is currently facing on the increases of domestic violence cases. To define about the domestic violence, usually intimate partners will be targeted as the perpetrators and victims. Thus, this paper will be discussing about the whole concept of domestic violence and various acts of civil law in handling such cases. The diversity of written laws imposes different punishment; therefore, it will determine whether the perpetrators will be facing either severe or light punishment. The article is written based on qualitative method. It can be concluded that domestic violence is applied on members in a family, intimate partner, children, and elderly. In addition, this article will focus on 3 acts of civil law which are Penal Code, Domestic Violence Act 1994 and Children Act 2001.